Aplicación del Design Thinking en el desarrollo y caracterización de conservas a base de chame (Dormitator latifrons) - Baren Sabando, María Lilisbeth (2024)
The research focused on developing chame preserves using Design Thinking to create new products with good nutritional quality. A Completely Randomized Design was employed with four treatments, each using different covering liquids (tomato sauce, spicy sauce, sunflower oil, and olive oil), with four repetitions, totaling 16 experimental units. Parameters such as pH (ranging from 5.8 to 6.35), drained weight (ranging from 35.60% to 44.14%), and NBTV (ranging from 14.01 mg/100g to 31.21 mg/100g) were analyzed, revealing statistically significant differences (p-value < 0.05) among the treatments. All treatments met the NTE INEN 1772:2013 standard for pH and NBTV. The microbiological analysis showed no presence of Clostridium botulinum, with T2 meeting both requirements. In the sensory evaluation, treatment T3 (sunflower oil) was preferred with the designation "like very much" in color, smell, and texture, followed by T4 (olive oil) with "like very much" in color, smell, and taste. However, there were no statistically significant differences in sensory perception among untrained tasters. In conclusion, the preserves developed using Design Thinking meet the market's required physical-chemical, microbiological, and sensory characteristics, resulting in an innovative product.